Auggie’s Motivation Facing Discrimination in Wonder Novel By R.J Palacio - Nurfajriani Nurfajriani; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2021)
This study aims to discover the type of discrimination experienced by Auggie and how the psychological aspects of Auggie based on Abraham Maslow's theory in Wonder novel by R.J. Palacio. The data source used in this study was the novel Wonder. In analyzing the data, the writer used a qualitative research method through a psychology approach. Data were obtained by using reading, noting, and analyzing techniques. While in classifying and analyzing data, the writer used Abraham Maslow's theory. The writer found that the novel Wonder by R.J Palacio contained 13 data indicating that the character experienced discrimination there were 6 data direct discrimination and 7 data indirect discrimination, and 25 data indicating the Hierarchy of human needs. This data is divided into 5 types of needs. The first need was physiological needs with 4 data, the second is safety needs with 4 data, love and belonging needs with 6 data, esteem needs with 7 data, and self-actualization needs with 5 data.